How do Overnight Stays React to Exchange Rate Changes? - Christian Stettler (Swiss Journal of Economics and Statistics, 2017)
This paper analyses the effect of a change in the real exchange rate on the number of overnight stays in Swiss hotels. It uses unique three-dimensional panel data on the monthly number of overnight stays by the visitor's country of origin in 141 Swiss communities during the ten-year period from January 2005 to December 2014. We find low exchange rate elasticities of 0.2 for cities, but much higher elasticities of 1.4 for touristic communities. On the source market side, we find large exchange rate elasticities for German, Dutch, and Belgian visitors, while travellers from France and Italy are less price sensitive.
Keywords: F14; F31; E52; Z31; 330; Real exchange rate; tourism; overnight stays; Swiss Franc; Switzerland